The upsetter the life & music of Lee Scratch Perry - Higbee, Ethan; Lough, Adam Bhala 1979-; Toro, Benicio del 1967-; Perry, Lee 1936-2021 (MVD Visual, 2011)
"The Upsetter tells the fascinating story of Lee Scratch Perry a visionary Jamaican musician, artists, prophet and madman, in his own words, through an exclusive interview given to the filmmakers at Scratch's home in Switzerland. Narrated by Academy Award winning actor Benicio Del Toro, The Upsetter is equally a documentation of 30 years of Jamaican music and culture and a character study of one of the most creative and inspiring human beings alive today"--Container
Keywords: Perry, Lee -- 1936-2021; Perry, Lee / 1936-; Reggae music / Jamaica; Reggae music; Jamaica; Biographical films; Documentary films; Film; DVD-Video